Adsorption and desorption of hexavalent chromium in miners wastes - Rodríguez, Roberto (2009)
The aim of this work is the evaluation of both adsorption-desorption mechanisms of hexavalent chromium in two metallurgical wastes. These processes were investigated using batch tests. Theses wastes correspond to the metallurgical processes of Ni-Co recovery in Cuban industries. The first one (called SAL-waste) is originated by sulphuric acid leaching and the second one (ACL-waste) is the by-product of ammonia-carbonate metallurgical leaching. The wastes are mainly constituted by iron minerals. Grain size distribution is poorly graded with a average value of diameter is about 0.02 mm. The adsorption isotherms of Cr in ACL and SAL are strongly non-linear and well described by the Freundlich equations (S = Kf Cn w). Desorption isotherms of Cr in both wastes are near-linear and illustrate very well the presence of a hysteretic process. The time of Cr adsorption short and desorption is very fasten. According these results the adsorption of chromate under acid conditions can be attributed to the favourable electrostatic interaction due to mineralogical composition of these wastes. The value of Kd of Cr in SAL waste were more than one order of magnitude that in the ACL. SAL waste can be effectively used to immobilize Cr(VI) and based on the elevated values of sorption capacity and the big stocks it has an attractive potential as a low cost treatment raw material for metal bearing effluents treatment.